2019
DOI: 10.12688/wellcomeopenres.14977.1
|View full text |Cite
|
Sign up to set email alerts
|

No effect of tranexamic acid on platelet function and thrombin generation (ETAPlaT) in postpartum haemorrhage: a randomised placebo-controlled trial

Abstract: Background:Postpartum hemorrhage (PPH) is a leading cause of maternal mortality and morbidity. The WOMAN trial showed that tranexamic acid (TXA) reduces death due to bleeding in women with PPH. To determine whether TXA has pro-thrombotic effects in women with PPH, we measured endogenous thrombin potential (ETP), coagulation factors V, VIII, von Willebrand (vW), fibrinogen, D-Dimers and platelet function.Methods: We conducted a sub-study within the WOMAN trial, an international randomized, parallel-group, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Endogenous thrombin potential in mice that received emicizumab only was 363±130 nm.min (mean±SD) and 363±95 nm.min in those treated with emicizumab+TxAc ( P > .05, Mann Whitney U test). In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity 13,14 . We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII 2 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Endogenous thrombin potential in mice that received emicizumab only was 363±130 nm.min (mean±SD) and 363±95 nm.min in those treated with emicizumab+TxAc ( P > .05, Mann Whitney U test). In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity 13,14 . We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII 2 .…”
Section: Resultssupporting
confidence: 89%
“…In accordance with previous clinical studies, the suppression of fibrinolytic activity by TxAc has no additional procoagulant effect on thrombin generation capacity. 13,14 We previously showed that thromboelastography was very sensitive to the TxAc effect; curves and thromboelastography parameters could be fully normalized with TxAc alone without any contribution from exogenous factor VIII. 2 However, this observation is inconsistent with clinical experience where TxAc alone is not usually sufficient to control bleeding in patients with severe haemophilia A.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, TXA therapy for orthopedic surgery does not alter prothrombin fragment 1.2 levels 39 and TXA therapy for postpartum hemorrhage does not significantly alter PPP TG. 40 We conclude that QPD results in a platelet-specific defect in TG, proportionate to the loss of platelet FV, suggesting that platelet FV, and possibly other α-granule proteins, are important to maximize TG, even when plasma FV is present. Additionally, the fibrinolytic inhibitor drug TXA improves TG for both control and QPD PRP and PPP samples, although TXA therapy appears to have little impact on QPD TG findings.…”
Section: Discussionmentioning
confidence: 73%
“…PRP TG has not been evaluated during TXA therapy for surgical, traumatic, or postpartum bleeding. Nonetheless, TXA therapy for orthopedic surgery does not alter prothrombin fragment 1.2 levels 39 and TXA therapy for postpartum hemorrhage does not significantly alter PPP TG 40 …”
Section: Discussionmentioning
confidence: 97%
“…In our preliminary experiments usign a 48-hour TnxAc regimen in non-septic mice, thrombocytopenia was not observed, but TAT levels were mildly, but significantly increased, suggesting that the those dose regimens of TnxAc were sufficient to change the hemostatic balance towards a status of higher thrombin abundance. Of note, recent studies using TnxAc in therapeutic doses failed to show any procoagulant effect of this agent [37], although increased TAT levels have been described in TnxAc-treated patients in the past [38]. Since indirect markers of thrombin generation such as TAT and D-dimer are early and sensitive markers of DIC, and TnxAc has been shown to increase organ damage in murine endotoxemia [39], the observed increase in TAT levels in TnxAc-treated mice do not allow us to exclude that TnxAc could be deleterious during sepsis.…”
Section: Discussionmentioning
confidence: 99%